Saudi Arabia’s Niche Diplomacy: A Middle Power’s Strategy for Global Influence - Mordechai Chaziza; Carmela Lutmar (World, 2025)
Saudi Arabia has emerged as a key middle power, leveraging niche diplomacy to expand its global influence. This study examines how the Kingdom strategically employs mediation, religious diplomacy, humanitarian aid, energy leadership, and sports diplomacy to shape regional and international dynamics. Unlike great powers, middle powers focus on specialized areas where they hold a comparative advantage, allowing them to exert influence despite material constraints. Saudi Arabia’s diplomatic recalibration aligns with its Vision 2030 agenda, prioritizing economic diversification, regional stability, and multilateral engagement. Saudi Arabia enhances its geopolitical significance by positioning itself as a mediator in regional conflicts, reinforcing its religious leadership, investing in sports diplomacy, and maintaining energy dominance. This study contributes to understanding middle power strategies in international relations, highlighting Saudi Arabia’s role as a stabilizing force in an evolving global order.